Predictions of radiation pattern and in–out asymmetries in the DEMO scrape-off layer using fluid neutrals. (1st May 2022) - Aho-Mantila, L.; Subba, F.; Bernert, M.; Coster, D.P.; Wiesen, S.; Wischmeier, M.; Bonnin, X.; Brezinsek, S.; David, P.; Militello, F.; The ASDEX Upgrade Team,; The EUROfusion MST1 Team,
Abstract: Strongly radiating and detached high-power discharges in present-day full-metal tokamaks have a characteristic radiation pattern involving condensation of radiation near the X-point, with significant radiative losses above the X-point. In contrast, Demonstration Fusion Power Plant (DEMO) divertor exhaust scoping studies using reduced physics models, including a fluid description for the neutrals, place the strongest radiation fronts in the divertor legs, near the separatrix. The present contribution studies sensitivity of the radiation pattern corresponding to maximal divertor impurity radiation to those physics models that are typically neglected in the simulations due to their computational expense: cross-field drifts, complex impurity models and kinetic neutrals. Model benchmarking is carried out in comparison to L-mode discharges, which are shown to feature both divertor and X-point radiation. The simulated plasma conditions with maximal divertor radiation have in–out asymmetries in the divertor legs and at the divertor entrance, and the asymmetries and the radiation patterns are observed to be sensitive to both cross-field drift effects and the neutral model. DEMO simulations, carried out using SOLPS-ITER, show an impact of cross-field drifts on the divertor asymmetries, but the impact is not large enough to move the radiation front from the divertor legs to regions above the X-point.